HIV-1 Tat: Role in Bystander Toxicity - Ajasin, David; Eugenin, Eliseo A. (Frontiers in Cellular and Infection Microbiology, 2020)
HIV Tat protein is a critical protein that plays multiple roles in HIV pathogenesis. While its role as the transactivator of HIV transcription is well established, other roles associated with several HIV-associated comorbidities are becoming more apparent in the current antiretroviral therapy (ART) era. HIV Tat protein is produced and released into the extracellular space from cells with active HIV replication or from latently infected cells into neighboring uninfected cells even in the absence of active HIV replication due to effective ART. Neighboring uninfected and HIV-infected cells can take up the released Tat resulting in upregulation of inflammatory genes and cytotoxicity. Some of these Tat-induced upregulated genes, especially pro-inflammatory cytokines and other factors, promotes several co-morbidities such as HIV associated neurocognitive disorder (HAND), HIV associated cardiovascular impairment, and accelerated aging. Thus, understanding how Tat modulates host and viral response is important in designing novel therapeutic approaches to limit the damage from HIV infection and the bystander consequences of secreted Tat.